Alterations of a spectrum of driver genes in female Chinese patients with advanced or metastatic squamous cell carcinoma of the lung. Issue 2 (February 2015) - Qiong, Zhao; Na, Wang Yi; Bo, Wang; Zhu, Zeng; Ling, Peng; Bo, Mou Hai; Min, Tang Ye; Lei, Zeng; Na, Hu Dan; Bo, Zhao; Fang, Liu Jun; Seng, Zheng Shu
Highlights: We analyzed molecular abnormalities in Chinese females with advanced SQCLC. Three specificities of female SQCLCs were observed: less smoking history, younger age and more peripheral type. No significant differences in EGFR, KRAS, EML4-ALK, PTEN and FGFR1 between different genders were found. Significant lower frequency of PIK3CA mutation was detected in females. Abstract: Objectives: Female patients with squamous cell carcinomas of the lung (SQCLC) in China differ from male patients in that most females are life-long never/light smokers. We hypothesized that the clinical characteristics and mutation profiles of a spectrum of driver genes in Chinese female patients with advanced SQCLC would also differ from those of male patients. Patients and methods: We examined the pathological subtype of SQCLC retrospectively by immunohistochemistry (IHC) and screened 38 female and 40 male patients with IIIB/IV-stage SQCLC in China from 2009 to 2012. Mutation analyses of EGFR, PIK3CA, KRAS, and PTEN were performed using PCR-based DNA sequencing. FGFR1 amplification and ALK rearrangements were detected by fluorescent in situ hybridization (FISH). A Cox regression model was used to assess the association between clinical features and genomic mutation status. Results: There were significantly fewer female patients with a history of smoking than males (5.3% vs. 90%; P < 0.001). A younger average age at diagnosis (54.5 vs. 61 years; P = 0.032) and a higher percentage of peripheral-type disease (47.4% vs. 25.0%; P = 0.040) were observed in females. No difference in ECOG score, tumor size, metastatic status, or overall survival between females and males was seen. PIK3CA mutations were significantly less common in female patients than males (0/38 vs. 6/40; P = 0.026). However, no significant difference in the mutational frequencies of EGFR, KRAS, PTEN, ALK, or FGFR1 was observed between females and males. Conclusions: Our data demonstrated that female patients with SQCLC are apparently a subtype, with a significantly lower percentage having a smoking history, a younger average age at diagnosis, a higher percentage of peripheral-type disease on radiological presentation, and a lower frequency of PIK3CA mutations. Given the similar survival outcomes between the genders, whether it is a distinct disease entity needs to be studied further in larger populations.